THE QUALITY OF LOCAL RABBIT MEAT (Lepus nigricollis) GIVEN BASIC FEED OF THE WASTE OF CARROT LEAVES (Daucus carota L.) SUPPLEMENTED WITH DIFFERENT LEVEL OF CONCENTRATE - I. B. G. S., Arsana; Sriyani, N. L. P.; Nuriyasa, MD. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
The study which aims at observing on the quality of local rabbit meat which was given concentrates at different levels with the basic feed of the waste of carrot leaves was conducted in Dajan Peken Village, Tabanan District, Tabanan Regency and nurtured for 12 weeks. A randomized group design with five replication was applied in this study. The rabbits were allocated randomly into four treatments, i.e. the rabbits were supplemented with control ration of carrot leaves (R0), control ration that was concentrated 15g /head /day (R1) control ration that was concentrated 30 g/head /day (R2) and control ration that was concentrated 45 g/ head /day (R3). The carrot leaves and water were  given continuously ( ad_libitum ). The variables which were observed in terms of; meat color, Ph value of the meat, the water holding capacity, the cooking loss and the drip loss. This study showed that R3 treatment caused significant differences in terms of meat color, Ph value of the meat and water holding capacity (P <0.05) compared to the treatments R0, R1, and R2. The results were not significantly different (P> 0.05) indicated by the test results of cooking loss and drip loss. In order to sum up, based on the results of this study, a conclusion can be made in which it shows that the quality of local rabbit meat given with the basic feed of the waste of carrot leaves which was supplemented with 45 g/ head/ day of concentrate was found having the best meat quality compared to rabbits without concentrate supplementation, in concentrate supplementation 15 g/ head/ day and 30 g/ head/ day. Keywords: local rabbit, concentrate, carrot leaves, meat quality